UNICONE PLUS VS. UNICONE - IN VITRO CYCLIC FATIGUE STUDY AT DIFFERENT ENVIROMENTAL TEMPERATURES - A. Jusku; P. Jirásek; A. Petřivalská; M. Rosa; J. Staněk; Ľ. Harvan (Czech Dental Chamber, 2020)
Introduction, aim: The issue of fracture of endodontic nickel-titanium instruments is quite extensive. It is an alloy that has the ability to change its internal structure. A great deal of effort is devoted to the development of an alloy with ideal properties. Instruments fracture occurs for two basic reasons. The first one is exceeding the limit of resistence of the instrument to cyclic fatigue and the other one is exceeding the limit of torsional load of the instrument. Most authors agree, that the main factor influencing instruments fracture is exceeding the limit of cyclic fatigue. The aim of this study was to evaluate the resistence to cyclic fatigue of the Unicone Plus in comparison with its predecessor, Unicone, under different enviromental conditions. Methods: A total of forty (20 + 20) Unicone 6/025 and Unicone Plus 6/025 instruments (Medin, Czech republic) with identical tip diameter of 0.25 mm and constant taper of 0.06 were subjected to cyclic fatigue test at temperatures 20 °C ± 1 °C and 35 °C ± 1 °C. Special device was constructed for testing. This device uses the principle of using an artificial root canal made of stainless steel with a radius of the curvature of 5 mm, an angle of curvature of 60°. A thermostatic bath was added to the set-up. The liquid of the desired temperature was added to the container and maintained at that temperature throughout the test under the control of an infrared thermometer. Due to the fact that tested instruments are used in reciprocal movement, they were tested in Reciproc ALL mode. To evaluate cyclic fatigue of the instruments, the time was measured from the start of rotation of the instrument, until the fracture occured with an accuracy of whole seconds. The non-parametric Kruskal-Wallis test was used for statistical evaluation, followed by Mann-Whitney U-tests of multiple comparison and Bonferroni correction at the significance level of 5%. Results: The obtained results from four groups were compared. Unicone instruments were statistically significantly less durable than Unicone Plus at both temperatures tested (p < 0.05). Higher enviromental temperature had statistically significant effect on lowering of cyclic fatigue resistence (p < 0.05). Conclusion: Unicone Plus instruments are more resistant to cyclic loading than Unicone. In this case, greater durability is most likely associated with innovative manufacturing processes. Furthermore, the resistence of instruments to cyclic fatigue dereases with increasing ambient temperature.